Kolaborasi Mahasiswa dan Masyarakat dalam Mewujudkan Ekonomi Berkeadilan melalui Program Pasar Murah - Haq, Alfiyyah Dhiya'ul; Salsabilla, Tarisya Zahwa; Alfarikhi, Muhammad Solakhuddin; Liberte, Iman Aji; Jundana, Kholid; Fiddien, Hasna Abidah; Halimah, Hajar Nisa'ul; Salwa, Salwa; Putra, Sudarmadi (Universitas Pahlawan Tuanku Tambusai, 2026)
Economic inequality remains a major challenge in achieving social welfare and distributive justice in Indonesia. According to data from the Central Bureau of Statistics in 2025, the Gini ratio of 0.375 indicates that income distribution among social groups has not yet been optimal. This condition highlights the need for an empowerment model that is not only economically oriented but also grounded in the values of social justice. This community service program aims to analyze the role of university students as agents of change through the implementation of a low-cost market program in supporting the concept of equitable economics. The program was carried out using a participatory approach involving the community and local entrepreneurs in distributing subsidized basic needs. The results show that the low-cost market contributed to improving the welfare of low-income communities while fostering students’ critical awareness of social justice and collaboration. This activity underscores the importance of integrating Islamic values into the practice of equitable economics based on community participation.